Peranan kredit skala kecil dan usaha bersama dalam pengembangan peluang kerja sektor non pertanian pedesaan Jawa Barat : studi kasus Badan Koordinasi Koperasi Kredit Bogor-Banten - Bagdja, Moehammad Ferry (Project working paper series / West Java Rural Nonfarm Sector Research Project ;, 1992)
Purpose of Badan Koordinasi Koperasi Kredit Bogor-Banten, Bogor-Banten Regional Cooperation Board for Credit Cooperatives to raise community welfare through process of education in economic activities in rural nonfarm areas of Jawa Barat Province; case study.